LANGUAGE STYLE AT ADVERTISEMENT IN CNN - Ananda Dwi Putri Caesary; La Sunra; Yunitari Mustikawati (Journal of English Literature and Linguistic Studies, 2022)
Language is very important in conveying the right information with the aim of influencing the individual. Advertising language shows more persuasive, attracts people's attention, and is creative. More attractive and creative advertising can influence more people to try these advertisements. This study focused on the category of language style and how the use of advertising formula in conveying message of the advertisement on CNN. The purpose of this study is to identify and describe the types of language style in advertisement on CNN and to explore how the use of advertising formulas convey messages in advertisement on CNN to viewers. In conducting this research, the researcher used qualitative research and descriptive methods. The advertisements were taken randomly from as many as 13 advertisements from three videos on commercial breaks channel. The results of this study show that there were 4 categories of language style used in advertisements on CNN, namely the morphological style, syntactical style, rhetorical style, and sloganized style. Advertisement on CNN uses a different type of language style. In terms of morphological category, advertisement on CNN uses simple and formal language, misspelling or coinage, loanword, the use of verb, and the use of adjectives. In terms of syntactical category, advertisement on CNN uses interrogative sentences and imperative sentence. In terms of rhetorical category, advertisement on CNN uses simile, repetition, and rhyming. In terms of sloganized category, advertisement on CNN use slogan and taglines. Furthermore, there were 6 advertising formulas used in advertisement, namely, soft sell, slice of life, comparison, straightforward, demonstration, and spokesperson.